2013
DOI: 10.1016/j.jse.2013.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical therapy in treating atraumatic full-thickness rotator cuff tears: a multicenter prospective cohort study

Abstract: Purpose To assess the effectiveness of a specific non-operative physical therapy program in treating atraumatic full thickness rotator cuff tears using a multicenter prospective cohort study design. Methods Patients with atraumatic full thickness rotator cuff tears who consented to enroll provided data via questionnaire on demographics, symptom characteristics, co-morbidities, willingness to undergo surgery, and patient related outcome assessments (SF-12, ASES, WORC, SANE score, Shoulder Activity Scale). Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
207
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(216 citation statements)
references
References 40 publications
1
207
1
7
Order By: Relevance
“…This treatment frequency is consistent with that reported in randomized controlled trials of manual physical therapy intervention, which typically involve 1 to 2 sessions per week for a total of 6 to 10 treatment sessions. 1,4,16,43,51,53 In a large, multicenter randomized controlled trial, a treatment plan similar to the one used in this case report was shown to be costeffective compared to usual care by a general practitioner in patients with knee and hip OA. 41 A unique aspect of the plan of care was the incorporation of booster sessions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This treatment frequency is consistent with that reported in randomized controlled trials of manual physical therapy intervention, which typically involve 1 to 2 sessions per week for a total of 6 to 10 treatment sessions. 1,4,16,43,51,53 In a large, multicenter randomized controlled trial, a treatment plan similar to the one used in this case report was shown to be costeffective compared to usual care by a general practitioner in patients with knee and hip OA. 41 A unique aspect of the plan of care was the incorporation of booster sessions.…”
Section: Discussionmentioning
confidence: 78%
“…4,19,28 An orthopaedic manual physical therapy approach, which combines manual physical therapy and reinforcing exercise tailored to the individual patient, has been shown to decrease pain and improve function in patients with subacromial impingement syndrome, atraumatic rotator cuff tears, and primary acromioclavicular joint pain. 4,5,21,24,29,43 In a recent pragmatic randomized controlled trial, patients with unilateral subacromial impingement syndrome, treated with either manual physical therapy or a corticosteroid injection, demonstrated significant improvements in pain and function that persisted at 1 year. 43 To our knowledge, peer-reviewed evidence supporting physical therapy intervention in the management of GHJ OA is absent.…”
Section: T T Outcomesmentioning
confidence: 99%
“…Future studies should further investigate this exercise program. Kuhn et al [55] conducted a multi-centre prospective cohort study of 381 patients who underwent physiotherapy over a 12-week period with a 2-year follow-up. The patients' compliance diaries showed a variation in programs from no therapy to supervision and home, home only, and supervision only.…”
Section: Physiotherapy Treatment Techniquesmentioning
confidence: 99%
“…Kuhn et al [55] conducted a study over a 3-month period and found that physiotherapy significantly improved pain, function and ROM. Wirth et al [95] conducted a similar study of 60 patients, with a 2-year follow-up.…”
Section: Patient Satisfaction Indicesmentioning
confidence: 99%
“…Surgical treatment may help on both counts. Nevertheless, three out of four patients with degenerative tears do well without surgery [27]. Choose wisely.''…”
Section: N 2012 the American Board Ofmentioning
confidence: 99%